The The effectiveness of audiovisual health education on knowledge and attitudes towards breast self-examination among female communication science students - Dia Yulikasari; Dwi Sri Handayani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Breast cancer is the most common type of cancer amon women in both developed and developing countries. In indonesian, breast cancer ranks first with 16.2% of cases in 2022. One way to prevent breast cancer is through early detection by performing breast self-examination (BSE). Improving knowledge and attitudes toward breast self-examination can be achieved through health education using various methods, one of which is audiovisual media. Purpose: To determine the effectiveness of health education using audiovisual media on the knowledge and attitudes of female Communication Science students towards breast self-examination. Method: This research design uses a quasi-experiment with a one-group pretest-posttest design. The sample in this study consisted of 41 female Communication Science students at 'Aisyiyah University Yogyakarta, selected using proportional random sampling. Data collection was conducted using questionnaires, and data analysis was performed using the Wilcoxon test. Results: The results of the analysis showed a significant increase in knowledge (p = 0.000 < 0.05) and attitude (p = 0.000 < 0.05) after intervention wuth audiovisual media. Conclusion: Health education using audiovisual media is effective in improving knowledge and attitudes toward breast self-examination among female students in the Communication Studies Program.